Violent Modernists The Aesthetics of Destruction in Twentieth-Century German Literature - Evers, Kai (Northwestern University Press, 2013)
Kai Evers's Violent Modernists: The Aesthetics of Destruction in Twentieth-Century German Literature develops a new understanding of German modernism that moves beyond the oversimplified dichotomy of an avant-garde prone to aggression on the one hand and a modernism opposed to violence on the other. Analyzing works by Robert Musil, Franz Kafka, Karl Kraus, Walter Benjamin, Elias Canetti, and others, Evers argues that these authors are among the most innovative thinkers on violence and its impact on contemporary concepts of the self, history, and society.